The New Russian Nationalism - Kolstø, Pal (Edinburgh University Press, 2016)
Assessing the transformation of Russian nationalist discourse in the 21st century Russian nationalism, previously dominated by 'imperial' tendencies - pride in a large, strong and multi-ethnic state able to project its influence abroad - is increasingly focused on ethnic issues. This new ethno-nationalism has come in various guises, like racism and xenophobia, but also in a new intellectual movement of 'national democracy' deliberately seeking to emulate conservative West European nationalism. Russia's annexation of Crimea in 2014 and the subsequent violent conflict in Eastern Ukraine utterly transformed the nationalist discourse in Russia. This book provides an up-to-date survey of Russian nationalism as a political, social and intellectual phenomenon by leading Western and Russian experts in the field of nationalism studies.